Bishop score versus transvaginal ultrasonographic measurement of cervical length in predicting successful labor induction in post-term pregnancy: prospective cohort study - Khalifa, Mansour A.; Abbas, Ahmed M.; Gaber, Mohammed A.; Salah, Maher (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The current study aims to compare the efficacy of Bishop score assessment and transvaginal ultrasonographic measurement of the cervical length in prediction of the outcome of labor induction in post-term pregnancy. Methods: A comparative Prospective observational study conducted in Department of Obstetrics and Gynecology, Kom Ombo central hospital from January 2017 to October 2017. Pregnant women were classified into two groups of Bishop Score Group (1): ladies with (Bishop Score <5) = unfavorable cervix and Group (2): those with (Bishop Score >5) = favorable cervix. Also, they were classified into two groups of cervical lengths: Group (1): women with (cervical length <25mm, shorter cervix) and Group (2): those with (cervical length ≥25 mm, longer cervix). The Primary outcome was Bishop score by digital examination and Cervical length by TVS. Results: The study group was 100 women. Regarding sonographic assessment, 44 patients had cervical length <25 mm and the mean cervical length for the whole study group was 25.19±8.16 mm. Successful induction was achieved in 78 patients (78%), while CS was done in 22 patients due to failed induction. No difference between both groups regarding the parity (p=0.063). When comparing women with successful VD versus those delivered by CS, we found significantly higher Bishop score in the first group 5.12 ± 1.93 vs 3.89 ± 1.71 in the second group (p=0.002). Additionally, VD group had significantly shorter cervix than CS group (22.31 ±7.14 vs. 35.37± 5.80 mm, p=0.007). The Bishop score showed significant moderate negative correlation with the cervical length (r=-0.589, p=0.001). Conclusions: Success of labor induction in women undergoing induction due to prolonged pregnancy can be highly predicted by cervical length as it is more objective and accurate than Bishop Score. The 25 mm cut-off point for cervical length was the best predictor of vaginal delivery.